2022
DOI: 10.1002/ajmg.b.32892
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of METTL3‐mediated m6A modification in depression‐induced cognitive deficits

Abstract: Depressive disorder (DD) is associated with N6-methyladenosine (m6A) hypermethylation. This study sought to explore the molecular mechanism of Methyltransferase-like 3 (METTL3) in cognitive deficits of chronic unpredictable mild stress (CUMS)-treated rats and provide novel targets for DD treatment. A DD rat model was established via CUMS treatment. Cognitive deficits were assessed via body weighing and behavioral tests. METTL3, microRNA (miR)-221-3p, pri-miR-221, GRB2-associated binding protein 1 (Gab1) exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…In addition, this upregulation of METTL3 could increase miR221-3p levels, leading to growth factor receptor-bound protein 2 associated binding protein 1 (Gab1s) inhibition. 357 Erasers. RNA modifications are removed by demethylases, allowing dynamic adjustment.…”
Section: Rna Modifications Participate In the Molecular Mechanisms Un...mentioning
confidence: 99%
“…In addition, this upregulation of METTL3 could increase miR221-3p levels, leading to growth factor receptor-bound protein 2 associated binding protein 1 (Gab1s) inhibition. 357 Erasers. RNA modifications are removed by demethylases, allowing dynamic adjustment.…”
Section: Rna Modifications Participate In the Molecular Mechanisms Un...mentioning
confidence: 99%
“…For example, major depressive disorder (MDD) is a mental health problem that is exhibited as an enormous impairment in mood, cognition, and memory and systemic inflammation, and it further harms hippocampal neurogenesis [ 41 ]. Niu et al reported that METTL3 was highly expressed in chronic unpredictable mild stress (CUMS)-induced MDD rats [ 42 ]. Further mechanic study found that METTL3-mediated m6A modification on pri-miR-221 promoted its processing and maturation that subsequently upregulated miR-221-3p expression to inhibit GRB2-associated binding protein 1 (Gab1) expression, which worsened the cognitive deficits in MDD rats [ 42 ] ( Figure 2 ).…”
Section: Mettl3 In Neuropathological Eventsmentioning
confidence: 99%
“…Niu et al reported that METTL3 was highly expressed in chronic unpredictable mild stress (CUMS)-induced MDD rats [ 42 ]. Further mechanic study found that METTL3-mediated m6A modification on pri-miR-221 promoted its processing and maturation that subsequently upregulated miR-221-3p expression to inhibit GRB2-associated binding protein 1 (Gab1) expression, which worsened the cognitive deficits in MDD rats [ 42 ] ( Figure 2 ).…”
Section: Mettl3 In Neuropathological Eventsmentioning
confidence: 99%
“…For METTL3, Xu et al (2022) found that the METTL3-specific deletion in the mouse hippocampus can induce the phenotype of depression-like behaviors and spatial memory reduction [18]. In contrast, another study on METTL3 reported to significant upregulation in the hippocampus of UCMS rats and contributed to their cognitive deficits (2022) [24]. For the inconsistent findings of FTO, downregulation expression of FTO was found in the hippocampus of depressed patients and mice exhibiting depressive-like behaviors [15].…”
Section: Hypericin Upregulated the Expression Of Mettl3 And Wtapmentioning
confidence: 99%